Designing Industry-Based Implementation Guidelines for Welding Engineering Expertise Programs in Vocational Education - Ryan Galih Wicaksono; Phil. Imam Mahir; Sugeng Priyanto (PT. Anagata Sembagi Education, 2026)
This study aimed to design industry-based implementation guidelines for welding engineering expertise programs in vocational education to improve graduate competency and workforce readiness. The research employed a Research and Development (R&D) approach involving vocational teachers, industrial practitioners, curriculum experts, and students. Data were collected through interviews, observations, questionnaires, document analysis, and focus group discussions. The findings revealed that industries require technical welding competencies, occupational safety skills, and professional soft skills. Based on these needs, implementation guidelines were developed covering curriculum organization, practical learning procedures, industrial collaboration, competency assessment, and safety standards. Expert validation results indicated that the guidelines were highly feasible and relevant for vocational education implementation. The study concludes that industry-based implementation guidelines can strengthen the alignment between vocational education and industrial requirements while enhancing practical competency development and graduate employability in the welding engineering sector.